A Novel Direct Butyrate Generator Reduces Belly Pain in a Randomized, Double-Blind, Placebo-Controlled Clinical Study - Edward Dosz; Devin Conley; Michael Lelah (Nutraceuticals)
This study aimed to evaluate the effects of ButyraGen®, a direct butyrate generator, on digestive health in a real-world setting. A 6-week, randomized, double-blind, placebo-controlled, virtual clinical study was conducted starting with 596 participants. Participants were randomly assigned to either the 200 mg ButyraGen® active or placebo group. Questionnaires were administered electronically to assess gastrointestinal health outcomes. Statistically significant improvements were observed in belly pain for the active ButyraGen® group compared with the placebo group, particularly in women, and particularly in post-menopausal women. The active group showed a higher likelihood of achieving clinically significant improvements in digestive health measures. ButyraGen® supplementation demonstrated statistically significant benefits in rapidly improving gastrointestinal health and quality of life, especially in women and those with upper and lower GI symptoms.